Skyskrapornas och de röda stugornas musik: Ett försök till förståelse av fusionen av jazz och svensk folkmusik - Burlin, Toivo (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2000)
This essay discusses the development of the Swedish “folk-jazz” concept through one of its most outstanding works, the 1965 record Adventures in Jazz and Folklore. The history of the production and the musical form of two of the record’s songs, “Lapp-Nils Polska” and “St. Örjanslåten”, are discussed. I here present a model for how this work can be studied as a result of three different closely related factors: 1. The “productivity” in jazz as a form and a way of creating music. This theory says that jazz as a product of different musical languages has developed into a form with a special openness to musical material of different kinds. 2. The changing musical traditions in the international jazz community in the late 1950s and early 1960s, for example, the exploration of meters other than 4/4, modality, and a growing interest in non-western musical traditions. In Sweden all these tendencies received their own development when Swedish jazz musicians turned their interest to Swedish folk music. 3. The very active folk-music politics of Ulf Peder Olrog at the Swedish Radio, and his non-romantic folk-music aesthetics, which in many ways corresponded to the jazz musicians attitudes’ toward this music.